Effectiveness Of Using The Application Duolingo To Improve Students’ Writing Skill - Maria Osmunda Eawea Monny; Evelyn Angelita Pinondang Manurung (Departement of Mathematics Education, 2024)
This research was conducted to determine the effectiveness of using the Duolingo application to improve students’ writing skills. The participants of this research are students of INSTIKI who are taking the subject Bahasa Inggris Dasar. The method used was Classroom Action Research and analyzed using Duolingo. The results showed significant progress in the pre-test, implementation, and post-test. The results showed that students writing skills in their application letters have improved much through the number of mistakes/errors. The results of this research have shown that the implementation of AI, especially the application of Duolingo and CAR has a good impact and positive outcomes to improve students’ writing skills. The results of Cycle I and Cycle II have shown that from 5 kinds of mistakes/errors, there were a significantly decreased number of errors that were: 1) prepositions from 20 to 5 errors; 2) agreement of numbers and nouns from 15 to 4 errors; 3) pronouns from 8 to 2 errors; 4) verbs from 20 to 6 errors; and 5) nouns from 20 to 8 errors. As students of IT College, the participants are encouraged to improve their skills in IT and foreign languages especially English. This finding has shown that the implementation of AI like Duolingo for IT Students is relevant to their field of study. in this digitalization era.